Glass-like transparent high strength polyethylene films by tuning drawing temperature. (8th May 2019) - Lin, Yunyin; Patel, Ruhi; Cao, Jun; Tu, Wei; Zhang, Han; Bilotti, Emiliano; Bastiaansen, Cees W.M.; Peijs, Ton
Abstract: High performance transparent polymeric materials are of great interests in many fields including automotive and electronics. Conventional transparent plastics like polycarbonate (PC) and poly(methyl methacrylate) (PMMA) possess relatively unsatisfactory mechanical performance, while high performance polymeric systems like solid-state drawn high-density polyethylene (HDPE) typically have an opaque appearance, limiting applications where both mechanical and optical properties are required. In this study, we successfully combined high transparency and high strength in HDPE films by carefully controlling processing parameters during solid-state drawing. By tuning the drawing temperature, highly oriented HDPE films with a transmittance of ∼90% are achieved even in the far field. Greater chain mobility at high drawing temperatures is believed to be responsible for fewer defects in the bulk and on the surface of the drawn films, resulting in less light scattering and hence high clarity. These highly transparent films possess a maximum Young's modulus of 27 GPa and a maximum tensile strength of 800 MPa along the drawing direction, both of which are more than 10 times higher than those of PC and PMMA. Results showed that a wide processing window ranging from 90 °C to 110 °C can be used to tailor the required balance between optical and mechanical performance. It is anticipated that these lightweight, low-cost, highly transparent, high strength and high stiffness HDPE films can be used in laminates and laminated composites, replacing traditional inorganic and polymeric glass for applications in automotive glazing, buildings, windshields, protective visors, displays etc. Graphical abstract: Image 1 Highlights: Transparent high strength polyethylene films are produced by regulating draw ratio and drawing temperature. The effect of drawing conditions on optical properties is systematically studied and optimized for the first time. The films show transparencies comparable to traditional inorganic and organic glass. The films possess tensile strengths greater than aluminium and steel.